The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/micr.22110
|View full text |Cite
|
Sign up to set email alerts
|

Posterior thigh perforator flaps: An anatomical study to localize and classify posterior thigh perforators

Abstract: In the last decade perforator flaps have been used increasingly for different indications. Many regions may serve as donor site. In this respect the posterior thigh region (PTR) has been neglected as a potential donor site for many years. The purpose of this study was to provide complete mapping of perforators supplying the posterior thigh region. Twelve fresh cadaver thighs were prepared injecting diluted acrylic paint into the iliac artery. Thereafter the posterior thighs were dissected from medial to latera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 34 publications
0
16
0
1
Order By: Relevance
“…20 The dominant blood supply of this anatomical area originates from the profunda femoris artery. 21 It runs distally and provides at least two perforators (85 percent of cases: three or more perforators) that are distributed evenly between the medial and lateral halves of the thigh.…”
Section: Discussionmentioning
confidence: 99%
“…20 The dominant blood supply of this anatomical area originates from the profunda femoris artery. 21 It runs distally and provides at least two perforators (85 percent of cases: three or more perforators) that are distributed evenly between the medial and lateral halves of the thigh.…”
Section: Discussionmentioning
confidence: 99%
“…Our earlier anatomical studies revealed longer and larger perforators in the posterior thigh region when compared with those in the anteromedial thigh region. 21,22 Previously reported average pedicle length of the PAP flap was 10.6 cm in a cadaveric study versus 9.9 cm in a clinical study ( Table 2). 19,20 In the current study, the average pedicle length was 11.0 cm.…”
Section: Discussionmentioning
confidence: 94%
“…In our initial experience, this original technique occasionally resulted in limited flap volume and caudal scar migration. Advancing on Allen's aforementioned work and our perforator studies of the leg, [21][22][23][24] we modified the PAP flap geometrically and applied it in a series of breast reconstruction cases.…”
mentioning
confidence: 99%
“…In addition, Hupkens et al. (, ) described a way to harden acrylic paint by leaving the limb in dry air for 1 day, followed by freezing for the next 2 days and thawing it for 1 or 2 days.…”
Section: Discussionmentioning
confidence: 99%